Injectable microsphere/hydrogel hybrid system containing heat shock protein as therapy in a murine myocardial infarction model. (November 2013) - Lee, Jangwook; Cha, Min-Ji; Lim, Kwang Suk; Kim, Jang-Kyung; Lee, Sang-Kyung; Kim, Yong-Hee; Hwang, Ki-Chul; Lee, Kuen Yong
Abstract Heat shock proteins, acting as molecular chaperones, protect heart muscle from ischemic injury and offer a potential approach to therapy. Here we describe preparation of an injectable form of heat shock protein 27, fused with a protein transduction domain (TAT-HSP27) and contained in a hybrid system of poly(d, l-lactic-co-glycolic acid) microsphere and alginate hydrogel. By varying the porous structure of the microspheres, the release of TAT-HSP27 from the hybrid system was sustained for two weeks in vitro. The hybrid system containing TAT-HSP27 was intramyocardially injected into a murine myocardial infarction model, and its therapeutic effect was evaluated in vivo. The sustained delivery of TAT-HSP27 substantially suppressed apoptosis in the infarcted site, and improved the ejection fraction, end-systolic volume and maximum pressure development in the heart. Local and sustained delivery of anti-apoptotic proteins such as HSP27 using a hybrid system may present a promising approach to the treatment of ischemic diseases.